A formação inicial de docentes da Educação Básica: significações das professoras sobre o estágio remunerado - Gonçalves, Liliane de Jesus (2024)
The present research aims to investigate, through (auto)biographical narratives, how teachers who graduated from paid internships with Special-Inclusive Education students in the municipality of Santo André mobilize their teaching practices based on their memories of initial training during the paid internship. The focus is to recover the memories of teachers who graduated from the optional paid internship in Special-Inclusive Education, with the aim of answering our central question: what are the possible contributions to the professional performance of teachers who graduated from the paid internship in Special-Inclusive education carried out in the municipality of Santo André? To this end, we conducted documentary research to elucidate the role of internships for Pedagogy students, the main course for the training of basic education teachers. It was investigated how the paid internship occurs and its role in the training of future teachers. Also sought to reference Special Education from an inclusive perspective, as this is the target audience of the studied paid internship. The research participants are two teachers who completed the paid internship during their undergraduate studies in the municipal education network of Santo André. They produced an account of their experiences as interns based on guiding questions and then participated in a narrative interview, where they had the opportunity to recount relevant aspects of the internship period and their teaching careers. The analysis of the account and the interview was conducted through Significant Themes, a form of analysis inspired by the cores of meaning from Aguiar and Ozella (2013). Through Significant Themes, we sought to grasp the senses and meanings constructed by the participating teachers regarding their work during the internship and in their current practice. The teachers' written and oral accounts showed that the internship was crucial for their teaching careers and that the knowledge acquired during this time is mobilized in their current practices. However, the accounts highlight important gaps that need to be addressed in the practice of paid internships, both concerning higher education institutions and the granting institution